The Application of Landsat 8 OLI to Identification Shoreline Change in 2000 – 2020 in Muncar Sub-District, Banyuwangi, East Java - Lutfiatul Janah; A Sediyo Adi Nugraha; Restu Ade Yanti; Lilis Nuraini (Universitas Pendidikan Ganesha, 2022)
The shoreline is a confluence between land and seawater used to determine the boundaries of a zone. This research was conducted on the coastline of Muncar Subdistrict, Banyuwangi, which aims to identify changes in the coastline of Muncar Subdistrict in 2000-2020 using Landsat image 8 OLI / TIRS, map the rate of changes in the coastline of Muncar Subdistrict in 2000 and 2020, and know the changes in the coastline in Muncar Subdistrict is more likely due to abrasion or accretion. The research methodology used for this study uses the NDVI analysis and the DSAS Shoreline analysis system. The identification takes 20 years with Landsat imaging in 2000 and 2020. The results of this study demonstrate that shoreline alterations are caused by abrasion, accretion and human activity. This change in shoreline results from abrasion and accretion factors. The coastline change in 2000-2020 in the subdistrict of Muncar can be concluded that there are six villages. These include the villages of Kumendung, Sumbersewu, Tembokrejo, Kedungrejo, Kedungwringin and Wringin Putih. However, the village most seriously affected by abrasion and accretion is Wringim Putih Village. The village of Wringin Putih reported that the level of abrasion and accretion could be considered 50 per cent abrasion and 50 per cent accretion. So the change in shoreline can result around the Muncar Subdistrict coastal area, such as reduced coastal areas, lost colonies, and damage to marine ecosystems